PENGARUH KOMPETENSI KEPRIBADIAN DAN SOSIAL GURU TERHADAP DISIPLIN BELAJAR SISWA DI SD NEGERI 1 PABUARAN WETAN - Nur Hasanah, Tania; Nurpratiwiningsih, Laelia; Tri Setiyoko, Didik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning discipline is an important factor in students' academic success, but its implementation is often influenced by teachers' characteristics. Teachers' personality and social competencies play a strategic role in fostering discipline through exemplary behavior and effective interactions. This study aims to analyze the simultaneous effect of teachers' personality and social competence on students' learning discipline at SD Negeri 1 Pabuaran Wetan. A quantitative correlational survey design was employed. The population consisted of 37 fifth-grade students. Data were collected through valid and reliable questionnaires and documentation and analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS). The findings revealed that teachers' personality competence did not significantly affect students' learning discipline, whereas teachers' social competence had a positive and significant effect. Simultaneously, both competencies significantly influenced learning discipline, with a significance value of 0.005 (<0.05) and a contribution of 26.5%. These findings indicate that improving teachers' personality and social competencies can enhance students' learning discipline. Therefore, teachers should continuously strengthen effective communication, positive interactions, cooperation with students, and professional competence to support a more disciplined learning environment.